Lipaleyrodes emiliae, a new species of whitefly (Hemiptera: Aleyrodidae) from Taiwan and Hong Kong - Chen, Chun-Hung; Ko, Chiun-Cheng (Zootaxa, 2006)
The adult male, female, immature stages, and egg of a new species of whitefly, Lipaleyrodes emiliae, are described from Taiwan and Hong Kong. The species has been found commonly on Emilia sonchifolia (Asteraceae). Scanning electron micrographs, photographs and drawings are included with descriptions of immature stages and adults. The immatures and adults of L. emiliae are compared with those of Bemisia tabaci.